Expression of nuclear matrix proteins binding matrix attachment regions in prostate cancer. PARP‐1: New player in tumor progression. Issue 7 (6th April 2015) - Barboro, Paola; Ferrari, Nicoletta; Capaia, Matteo; Petretto, Andrea; Salvi, Sandra; Boccardo, Simona; Balbi, Cecilia
<x xml:space="preserve">Abstract</x> Prostate cancer (PCa) displays infrequent point mutations, whereas genomic rearrangements are highly prevalent. In eukaryotes, the genome is compartmentalized into chromatin loop domains by the attachment to the nuclear matrix (NM), and it has been demonstrated that several recombination hot spots are situated at the base of loops. Here, we have characterized the binding between NM proteins and matrix attachment regions (MARs) in PCa. Nontumor and 44 PCa tissues were analyzed. More aggressive tumors were characterized by an increase in the complexity of the NM protein patterns that was synchronous with a decrease in the number of proteins binding the MAR sequences. PARP‐1 was the protein that showed the most evident changes. The expression of the PARP‐1 associated with NM increased and it was dependent on tumor aggressiveness. Immunohistochemical analysis showed that the protein was significantly overexpressed in tumor cells. To explore the role of PARP‐1 in PCa progression, PCa cells were treated with the PARP inhibitor, ABT‐888. In androgen‐independent PC3 cells, PARP inhibition significantly decreased cell viability, migration, invasion, chromatin loop dimensions and histone acetylation. Collectively, our study provides evidence that MAR‐binding proteins are involved in the development and progression of PCa. PARP could play a key role in the compartmentalization of chromatin and in the development of the more aggressive phenotype. Thus, PARP can no longer be viewed only as an enzyme involved in DNA repair, but that its role in chromatin modulation could provide the basis for a new therapeutic approach to the treatment of PCa.